Statin therapy lowers the risk of new-onset atrial fibrillation in patients with end-stage renal disease. (15th December 2015) - Ho, Li-Ting; Lin, Lian-Yu; Yang, Yao-Hsu; Wu, Cho-Kai; Juang, Jyh-Ming Jimmy; Wang, Yi-Chih; Tsai, Chia-Ti; Lai, Ling-Ping; Hwang, Juey-Jen; Chiang, Fu-Tien; Lin, Jiunn-Lee; Chen, Pau-Chung
Abstract: Objectives: The objective is to assess the effectiveness of statin use to prevent atrial fibrillation (AF) in dialysis patients. Methods: We used a database from the Registry for Catastrophic Illness from the National Health Research Institute (NHRI), which encompasses almost 100% of the patients receiving dialysis started from 1997 to 2008 in Taiwan. All dialysis patients aged 18 or older without history of cardiovascular events in 1997 and 1998 were incorporated. Finally, 113, 191 dialysis patients were enrolled. We used propensity score (PS) matching method and Cox's proportional hazard regression models to estimate hazard ratios for AF events for statin users vs. nonusers. Results: In statin group, the incidence of developing new AF was significantly lower than that in control group (1.1% vs. 3.8%, P < 0.001). The PS-based selection process identified 2146 patients receiving statins and 2146 who did not receive statins. The incidence of developing AF remained lower in statin group than that in control group (2.4% vs. 4.9%, P < 0.001). After PS matching, Cox's proportional hazard regression analyses showed that there was a protective effect of developing AF in a dose-responsive manner. The protective effect was more obvious in subjects with younger age, female gender, hyperlipidemia, coronary artery disease and peripheral artery disease and in subjects without taking angiotensin converting enzyme inhibitor and angiotensin receptor blocker. Conclusion: Our analyses showed that statin therapy was associated with lower risk of newly diagnosed AF in patients with dialysis.